Immune activation and paediatric HIV-1 disease outcome. Issue 2 (March 2016) - Roider, Julia M.; Muenchhoff, Maximilian; Goulder, Philip J.R.
Abstract : Purpose of review: The paediatric HIV epidemic is changing. Over the past decade, new infections have substantially reduced, whereas access to antiretroviral therapy (ART) has increased. Overall this success means that numbers of children living with HIV are climbing. In addition, the problems observed in adult infection resulting from chronic inflammation triggered by persistent immune activation even following ART mediated suppression of viral replication are magnified in children infected from birth. Recent findings: Features of immune ontogeny favour low immune activation in early life, whereas specific aspects of paediatric HIV infection tend to increase it. A subset of ART-naïve nonprogressing children exists in whom normal CD4 + cell counts are maintained in the setting of persistent high viremia and yet in the context of low immune activation. This sooty mangabey-like phenotype contrasts with nonprogressing adult infection which is characterized by the expression of protective HLA class I molecules and low viral load. The particular factors contributing to raised or lowered immune activation in paediatric infection, which ultimately influence disease outcome, are discussed. Summary: Novel strategies to circumvent the unwanted long-term consequences of HIV infection may be possible in children in whom natural immune ontogeny in early life militates against immune activation. Defining the mechanisms underlying low immune activation in natural HIV infection would have applications beyond paediatric HIV.